Framing the human-technology relationship: How Religious Digital Creatives engage posthuman narratives. (September 2016) - Campbell, Heidi A
This article highlights the fact that careful study of common posthuman outlooks, as described by Roden (2015), reveals three unique narratives concerning how posthumanists view the nature of humanity and emerging technologies. It is argued that these narratives point to unique frames that present distinct understandings of the human-technology relationship, frames described as the technology-cultured, enhanced-human, and human-technology hybrid frames. It is further posited these frames correlate and help map a range of ways people discuss and critique the impact of digital culture on humanity within broader society. This article shows how these frames are similarly at work in the language used by Religious Digital Creatives within Western Christianity to justify their engagement with digital technology for religious purposes. Thus, this article suggests careful analysis of ideological discussions within posthumanism can help us to unpack the common assumptions held and articulated about the human-technology relationship by members within religious communities.